Pengaruh Electronic Word of Mouth (E-WoM) Terhadap Keputusan Pembelian (Studi Kasus pada Konsumen HRD Coffee Soreang) - Gusmiawati, Gusmiawati; Dewi, Lies Anggi Puspita (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Social media is currently a source of information obtained by people to find information about a place they will visit. This phenomenon can be called electronic word of mouth or stories that someone shares in electronic media. The information that has been obtained will be taken into consideration in determining purchasing decisions. Consumer purchasing decisions will always adjust to consumer circumstances, where if consumers are satisfied with the first purchase experience, consumers will make purchases repeatedly. This study aims to determine whether electronic word of mouth can influence consumer purchasing decisions at HRD Coffee. Using quantitative methods with primary and secondary data collection. The population in this study were HRD Coffee consumers with 96 samples with simple regression analysis analyzed using SPSS. The results of this study prove that electronic word of mouth spread to consumers is able to have a positive and significant influence on consumer purchasing decisions at HRD Coffee. With that, it is hoped that HRD Coffee Soreang can improve its performance and create a more positive impression in the eyes of customers.